Analysis of Rural Plant Landscapes in Yueqing: A Case Study of Yandang Mountain - Zhao, Jiawen (International Journal of Natural Resources and Environmental Studies, 2025)
To investigate the technique of developing rural plant landscapes against the backdrop of urbanisation, this study uses Yandang Mountain in Yueqing City, Zhejiang Province, as a case study. Through field research and type analysis, we methodically categorised the spatial characteristics of the production-living-ecological space of rural plant landscapes in Yandang Mountain, as well as their current state, from the perspective of integrating ecological, living, and production spaces in the countryside. According to the study, the five principles of wholeness, culture, ecology, pragmatism, and art should be combined with native plant resources to maximise plant configuration and landscape structure. The findings demonstrate that by encouraging industrial integration, maximising living space, and preserving ecological balance, Yandang Mountain can achieve the multiple benefits of plant landscapes in environmental conservation, economic development, and cultural heritage. It has been determined that rural plant landscapes are a key component of rural rehabilitation, and Yandang Mountain’s landscape development practices offer a model for similar areas.